Sistemas de Puesta a Tierra: Diseñado con IEEE-80 y evaluado con MEF (2010)
Precisar el modelo y la medición del sistema de puesta a tierra en una subestación es de vital importancia para garantizar la operación del sistema. Las reglas enumeradas en la forma IEEE 80 y la introducción al, método de los elementos finitos para el cálculo de la distribución son el centro del análisis de este libro. Actualmente es de suma importancia entregar las curvas de distribución de potencial en los electrodos del sistema para la correcta evaluación del valor de la resistencia del sistema. Los científicos basan el actual modelo de la estructura de los puntos medidos sobre el sólido, tratamiento que se ha intentado narrar en el texto / Abstract: How to precisely the model and measure the grounding resistance of substations is the fundamental factor to guarantee the safe operation of power systems. The placement rules of IEEE STD 80 and test electrodes for the grounding resistance measurement of grounding system in vertical-layered soil were analyzed by the numerical method in this book. The actual demanded location of the test potential electrode respective to the true grounding resistance of grounding system in the different measuring directions changed (in a wide range)when the grounding system was arranged in different soil models this is the principal idea for the introduction of the FEM ï¿½finite elements method in the IEEE std 80. The scientific and suitable measuring method of grounding resistance is based on analyzing the actual soil model and the grounding system structure to obtain the suitable test route and choose the correct compensated point location of the potential electrode.